Physico-chemical characterization, bioactivity evaluation and cytotoxicity of PDA nanoparticles doped tricalcium silicate cements. Issue 2 (15th January 2022) - Wu, Meng; Müller, Lenka; Schilling, Tatjana; Gbureck, Uwe; Wang, Tao; Müller, Frank A.
Abstract: The long setting time and insufficient strength of tricalcium silicate (TCS)-based cements are a main disadvantage for their clinical use. Therefore, the aim of this study was to develop an advanced TCS cement by incorporating polydopamine (PDA) nanoparticles. The setting time and compressive strength of TCS cement with incorporated PDA nanoparticles were evaluated. Furthermore, the effect of PDA nanoparticles on the apatite formation and the cytotoxicity of hydrated cements was investigated. The results show that the initial and final setting time of the cements were reduced by 63.9% and 46.7%, respectively, by adding 4 wt% PDA nanoparticles. The compressive strength of the cements reached 39.6 MPa by the addition of 4 wt% PDA and was thus 37.5% higher than that of pure TCS. Furthermore, the apatite-forming ability was also improved with the incorporation of 4 wt% PDA and the good biocompatibility was readily confirmed by using a fibroblast cell line. Our results showed that a TCS cement reinforced with PDA nanoparticles could be a promising dental restorative material.